2018
DOI: 10.1071/cp17309
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of lentil varieties and farming system effect on seed damage and yield loss due to bruchid (Bruchus spp.) infestation

Abstract: A major constraint of lentil (Lens culinaris Medik.) cultivation is yield reduction due to field infestation by the seed beetles Bruchus spp. (bruchids). The aim of the study was to assess seed loss (SL) and yield loss (YL) due to bruchid infestation under organic and conventional farming, and to investigate genotypic variability for seed yield of 20 lentil varieties in response to bruchid damage. Field experiments were established over three consecutive years in two areas of central and northern Greece. SL wa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
8
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 20 publications
2
8
0
1
Order By: Relevance
“…This study was not designed to include the farming system as a source of variation; however, our results demonstrated that SY was affected by the farming system. These results were also confirmed in previous studies [ 42 , 43 , 44 ] although genotypic response within farming system was not thoroughly studied. Under organic farming conditions and across the five lentil genotypes, the most productive environment was E8 (2.28 t ha −1 ) which corresponded to location Orestiada/2020, followed by E3 (1.88 t ha −1 ) (Thessaloniki/2019) and E4 (1.87 t ha −1 ) (Orestiada/2019).…”
Section: Discussionsupporting
confidence: 89%
“…This study was not designed to include the farming system as a source of variation; however, our results demonstrated that SY was affected by the farming system. These results were also confirmed in previous studies [ 42 , 43 , 44 ] although genotypic response within farming system was not thoroughly studied. Under organic farming conditions and across the five lentil genotypes, the most productive environment was E8 (2.28 t ha −1 ) which corresponded to location Orestiada/2020, followed by E3 (1.88 t ha −1 ) (Thessaloniki/2019) and E4 (1.87 t ha −1 ) (Orestiada/2019).…”
Section: Discussionsupporting
confidence: 89%
“…Valuable genotypic variability was observed with respect to both seed and yield losses. Farming system was the main source of variation for both losses, while early flowering and small seed size were traits associated with low losses (Vlachostergios et al 2018). Lentil yield loss from the competition with weeds can range as high as 80% (Pala 2019).…”
Section: Reduction In Yield and Quality Due To Biotic Stressesmentioning
confidence: 99%
“…Vlachostergios et al. (2018) found that lentils, depending on variety, can adopt two main strategies, that is, fast growth rate or high harvest index (HI), in response to bruchid damage; therefore, these specific traits should be carefully considered when choosing the variety to reduce yield loss. Considering weed control, Pannacci et al.…”
Section: Introductionmentioning
confidence: 99%
“…Lake and Sadras (2021) found that the selection of lentil genotypes with high growth rates could improve yield under stress. Vlachostergios et al (2018) found that lentils, depending on variety, can adopt two main strategies, that is, fast growth rate or high harvest index (HI), in response to bruchid damage; therefore, these specific traits should be carefully considered when choosing the variety to reduce yield loss. Considering weed control, Pannacci et al (2017Pannacci et al ( , 2018 reported on nonchemical weed management options for minor and legume crops and found that coupling split-hoeing and fingerweeding represents one of the best mechanical weed control options in organic cropping systems.…”
Section: Introductionmentioning
confidence: 99%